Forecasting the ranks of sites suitable for power plant installations (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2017)
An increase in the number of decision parameters used for ranking of sites for a power plant installation using the soft computing techniques leads to complex formulations that are computationally expensive[41]. Amongst a large number of decision parameters, if some of the parameters do not significantly contribute towards the ranking process, then we need not consider these for decision making. Moreover, it is very tedious to form fuzzy sets for all the 87 decision parameters from several environmental experts, which serve as inputs to certain soft computing techniques used for ranking. The decision parameters comprise of some parameters used to describe air quality, water quality, land suitability, socioeconomic and ecological suitability. We have made an attempt to reduce the number of input decision parameters so that the processing is computationally fast without significantly degrading the accuracy of the end results. We have also attempted to predict futuristic values of some of the relevant parameters to infer site suitability and/or ranking, futuristically (subsequent five years) which can act as a planning tool.